ÁP DỤNG PHƯƠNG PHÁP QUY HOẠCH THỰC NGHIỆM TRONG NGHIÊN CỨU CHẾ TẠO VẬT LIỆU BLEND BA CẤU TỬ TRÊN CƠ SỞ NBR – PVC – CR - Liên, Trần Kim; Hải, Phạm Hồng; Kháng, Đỗ Quang (Vietnam Journal of Science and Technology, 2012)
SUMMARY APPLICATION OF THE DESIGN OF EXPERIMENTS  IN THE PREPARATION OF RUBBER BLENDS BASED ON NBR, CR AND PVC The preparation of rubber blends which aims at having higher properties and reasonable cost, based on nitrile butadiene rubber (NBR), choloroprene rubber (CR) and PVC. By using the design of experiments, a mathematical model describing the relationship between the tensile strength y and compositions NBR (x1), PVC (x2), CR (x3) has been found. It has a form as follow: y =  14.2664x1 –  5.7154x2 + 13.028x3 + 2.0824x1x2 + 25.1865x1x3 + 0.925x2x3 + 262.3118x1x2x3 in the range of the variables: 0.2 ≤ x1 ≤ 0.6; 0.1 ≤ x2 ≤ 0.4, 0.2 ≤ x3 ≤ 0.5, and x1 + x2 + x3 = 1. The optimal conditions have been determined by the algorithm FLEXIPLEX of nonlinear programming